Shadow Banking and Market-Based Finance - Adrian, Tobias (Departmental Papers; Departmental Paper ;, 2018)
Variants of nonbank credit intermediation differ greatly. We provide a conceptual framework to help distinguish various characteristics-structural features, economic motivations, and risk implications-associated with different forms of nonbank credit intermediation. Anchored by this framework, we take stock of the evolution of shadow banking and the extent of its transformation into market-based finance since the global financial crisis. In light of the substantial regulatory and supervisory responses of recent years, we highlight key areas of progress while drawing attention to elements where work still needs to be done. Case studies of policy challenges arising in different jurisdictions are also discussed. While many of the amplification forces that were at play during the global financial crisis have diminished, the post-crisis reform agenda is not yet complete, and policy makers must remain attentive to new challenges looming on the horizon.